Immunologic and Protective Properties of Subunit- vs. Whole Toxoid-Derived Anti-Botulinum Equine Antitoxin - Alon Ben David; Ada Barnea; Amram Torgeman; Eran Diamant; Eyal Dor; Arieh Schwartz; Osnat Rosen; Noa Caspi; Miki Saraf; Elad Lerer; Yaakov Adar; Edith Lupo; et al. (Vaccines, 2022)
Botulism is a paralytic disease caused by botulinum neurotoxins (BoNTs). Equine antitoxin is currently the standard therapy for botulism in human. The preparation of equine antitoxin relies on the immunization of horses with botulinum toxoid, which suffers from low yield and safety limitations. The Hc fragment of BoNTs was suggested to be a potent antibotulinum subunit vaccine. The current study presents a comparative evaluation of equine-based toxoid-derived antitoxin (TDA) and subunit-derived antitoxin (SDA). The potency of recombinant Hc/A, Hc/B, and Hc/E in mice was similar to that of toxoids of the corresponding serotypes. A single boost with Hc/E administered to a toxoid E-hyperimmune horse increased the neutralizing antibody concentration (NAC) from 250 to 850 IU/mL. Immunization of naïve horses with the recombinant subunits induced a NAC comparable to that of horses immunized with the toxoid. SDA and TDA bound common epitopes on BoNTs, as demonstrated by an in vitro competition binding assay. In vivo, SDA and TDA showed similar efficacy when administered to guinea pigs postexposure to a lethal dose of botulinum toxins. Collectively, the results of the current study suggest that recombinant BoNT subunits may replace botulinum toxoids as efficient and safe antigens for the preparation of pharmaceutical anti-botulinum equine antitoxins.